2019
DOI: 10.1097/icb.0000000000000525
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Displacement of Limited Traumatic Submacular Hemorrhage Without Tissue Plasminogen Activator: A Case Series

Abstract: Pneumatic displacement is an effective technique in the management of SMH due to recent or old blunt trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In a case series of 3 patients with post-traumatic SMH, Balughatta et al [22] used 0.3 ml of intravitreal pure C3F8, obtaining significant displacement of the SMH and visual recovery in 2 of the 3 cases.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…In a case series of 3 patients with post-traumatic SMH, Balughatta et al [22] used 0.3 ml of intravitreal pure C3F8, obtaining significant displacement of the SMH and visual recovery in 2 of the 3 cases.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…The functional outcome may also be influenced by the duration and the size of submacular hemorrhage. Persistent SRMH damages the photoreceptors through three main mechanisms: iron-related toxicity, impairment of diffusion of oxygen and nutrition, and mechanical damage due to clot contraction [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique has become less common because it is associated with poor postoperative visual acuity and a high rate of retinal detachment [ 6 ]. Balughatta et al [ 5 ] recently reported a case series of C 3 F 8 pneumatic displacement of limited traumatic SMH with excellent anatomical results and final visual acuities attributed only to gas injection and patient positioning, without surgery or the use of tPA.…”
Section: Discussionmentioning
confidence: 99%
“…Blunt ocular trauma with SMH is a major cause of severe vision loss [ 4 ], usually affecting young patients and causing several pathological conditions such as commotion retinae, choroidal rupture, macular hole, subretinal and macular hemorrhage, retinal vascular rupture, vitreous hemorrhage, retinal pigment epithelial edema and healed scarring, retinal dialysis, macular infarction, traumatic optic neuropathy, optic nerve avulsion [ 2 ], and even retinal tears. Clinical and histopathological studies have shown that prolonged contact of the blood catabolic products with photoreceptors in the subretinal space worsens the prognostic and visual outcomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%